2010
DOI: 10.1177/104063871002200302
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Categorization of Contemporary H3N2 Swine Influenza Virus Isolates Using a High-Throughput Serum Neutralization Assay

Abstract: Abstract. In vivo, neutralizing antibodies are critical for viral clearance. A high-throughput serum neutralization (HTSN) assay was developed to antigenically categorize Swine influenza virus (SIV) isolates. Uncategorized viruses were tested using a panel of antisera representing the H3N2 SIV subtypes and the results expressed as a serum neutralization ratio. Antisera were generated against contemporary isolates representing circulating H3N2 SIV subtypes (clusters I, III, IV). Reference viruses and the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…One previous study suggested that the protein sequence identity could be used to differentiate antigenic clusters of H3N2 IAVs infecting swine (22). However, our results indicated that the rate of antigenic evolution among H3N2 swine-origin IAVs could be independent of the rate of genetic evolution and that the protein sequence similarity alone does not predict IAV antigenic relationships.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…One previous study suggested that the protein sequence identity could be used to differentiate antigenic clusters of H3N2 IAVs infecting swine (22). However, our results indicated that the rate of antigenic evolution among H3N2 swine-origin IAVs could be independent of the rate of genetic evolution and that the protein sequence similarity alone does not predict IAV antigenic relationships.…”
Section: Discussioncontrasting
confidence: 53%
“…Phylogenetic analyses of HA genes from H3N2 IAVs isolated from North American pigs after 1998 demonstrate that these trH3N2 IAVs can be classified into at least four genetic groups (clusters I, II, III, and IV) (21) with one lineage (cluster IV) predominating since 2005. Neutralization assays with swine antisera demonstrated that these four genetic clusters are also antigenically distinct (22). Several reassortment events between trH3N2 IAVs, human-origin IAVs, and classical swine influenza virus have occurred since 1998, resulting in multiple gene constellations with various HA and NA genes in combination with the triple reassortant internal gene (TRIG) cassette (which in-cludes PB2, PB1, PA, NP, NS, and M segments) (23,24).…”
mentioning
confidence: 99%
“…Swab samples were added to MDCK or swine testicle (ST) cells (American Type Culture Collection) as described ( 27 , 28 ). Virus isolates were identified by HA assay, as described in the World Health Organization manual on animal influenza diagnosis and surveillance ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…The HTSN assay was performed as previously described (11,12). Briefly, antisera were diluted 1:800 in DMEM, combined with 1,000 median TCID 50 of virus, and incubated at 37°C for 1 h. The virus-antiserum mixture was next transferred to a confluent monolayer of ST cells and incubated for 4 days at 37°C.…”
Section: Cells and Virusesmentioning
confidence: 99%